Application of Data Mining to Determine the Spread of Tuberculosis Disease in Bogor District - Ervansyah, Muhammad Ramlan; Fitriansyah, Aswin (International Journal of Law Social Sciences and Management, 2025)
Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis and transmission of tuberculosis easily occurs through the air. The prevalence rate of TB patients in Indonesia is estimated at 289 per 100 thousand population and the incidence is 189 per 100 thousand population. 27 out of 1,000 people are threatened with death and need an effective handling effort. The need for an effective handling effort to overcome the spread of TB, one of these efforts is by grouping the areas of TB disease spread in Bogor Regency. This grouping aims to find out which areas have high, medium, and low levels of tuberculosis cases. The results of this study are expected to be a recommendation for the Bogor Regency Government in handling TB more effectively.